2000
DOI: 10.1159/000057511
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Gas Phase Organic Emissions from Hot Cooking Oil in Commercial Kitchens

Abstract: A large quantity of oily fumes is generated in fast food and Chinese restaurants from cooking oil kept at a high temperature in the kitchens. If these oily fumes are not properly abated, they can be a major source of organic emissions in some dense urban areas with a lot of restaurants such as found in Hong Kong. In the present study, the most commonly used cooking oil, peanut oil, was kept at 260°C in an environment typical of a commercial kitchen that consisted of a two-burner stir-frying cooking range, a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…They are exposed to a wide range of occupational hazards such as cuts, burns, sprains and strains, slips and falls, [4][5][6] second-hand smoke, [7][8][9] and air pollutants including cleaning chemicals and emissions from cooking fume. [10][11][12][13][14] In addition, service employees are exposed to high noise levels during peak hours in the morning, during the lunch time, and in the evening hours that may affect psychological and physiological well-being. Unfortunately, the extant literature of noise primarily focused on industrial and environmental noise.…”
Section: Introductionmentioning
confidence: 99%
“…They are exposed to a wide range of occupational hazards such as cuts, burns, sprains and strains, slips and falls, [4][5][6] second-hand smoke, [7][8][9] and air pollutants including cleaning chemicals and emissions from cooking fume. [10][11][12][13][14] In addition, service employees are exposed to high noise levels during peak hours in the morning, during the lunch time, and in the evening hours that may affect psychological and physiological well-being. Unfortunately, the extant literature of noise primarily focused on industrial and environmental noise.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Weber-Fechner law, the relation between the odour intensity and concentration is expressed, as shown in Equation (1).…”
Section: Methods To Evaluate Food Odour Levelmentioning
confidence: 99%
“…Major sources of indoor odours are human occupants, environmental tobacco smoke and volatile building materials [15]. As significant as all those are pollutants generated during cooking [1][2][3][4][5][6].…”
Section: Researches For Odour Spread In Residential Buildingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one proposal, the ventilation's flow performance was enhanced by a change in hood structure [9][10][11][12][13][14][15] , and a method was developed to evaluate the performance rate of a Local Exhaust Ventilation [16][17][18] . Several studies reported measurements of the indoor air quality in kitchens using a local exhaust ventilation system [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%